Anti-Inflammatory Effects of a Polyphenol, Catechin-7,4'-O-Digallate, from Woodfordia uniflora by Regulating NF-κB Signaling Pathway in Mouse Macrophages - Eui Jin Kim; Ji Bin Seo; Jae Sik Yu; Seoyoung Lee; Jae Sung Lim; Jeong Uk Choi; Chang-Min Lee; Luay Rashan; Ki Hyun Kim; Young-Chang Cho (MDPI AG, 2021)
Inflammation is a defense mechanism that protects the body from infections. However, chronic inflammation causes damage to body tissues. Thus, controlling inflammation and investigating anti-inflammatory mechanisms are keys to preventing and treating inflammatory diseases, such as sepsis and rheumatoid arthritis. In continuation with our work related to the discovery of bioactive natural products, a polyphenol, catechin-7,4'-O-digallate (CDG), was isolated from Woodfordia uniflora, which has been used as a sedative and remedy for skin infections in the Dhofar region of Oman. Thus far, no study has reported the anti-inflammatory compounds derived from W. uniflora and the mechanisms underlying their action. To investigate the effects of CDG on the regulation of inflammation, we measured the reduction in nitric oxide (NO) production following CDG treatment in immortalized mouse Kupffer cells (ImKCs). CDG treatment inhibited NO production through the downregulation of inducible nitric oxide synthase expression in lipopolysaccharide (LPS)-stimulated ImKCs. The anti-inflammatory effects of CDG were mediated via the inhibition of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activation, an important inflammatory-response-associated signaling pathway. Moreover, CDG treatment has regulated the expression of pro-inflammatory cytokines, such as IL-6 and IL-1β. These results suggested the anti-inflammatory action of CDG in LPS-stimulated ImKCs.